Bifunctional porous iron phosphide/carbon nanostructure enabled high-performance sodium-ion battery and hydrogen evolution reaction - Lim, Yew Von (2020)
Transition metal phosphides, such as iron phosphide (FeP), have recently been studied as promising high performance active materials for sodium-ion batteries (SIBs) and hydrogen evolution reaction (HER) due to their excellent energy storage and conversion capabilities. To achieve long cycle lifetime, high rate sodium storage performance and stable HER reactivity, porous FeP/C nanostructures have been designed and synthesized through low temperature phosphorization of the Metal-Organic Framework (MOF) nanostructure. The resulting FeP/C composite consists of highly porous nanocubic structure with FeP nanoparticles distributing the carbon scaffolding, showing high surface area and small pore size distribution. This unique nanostructure enables fast and efficient electrons/ions transportation, and provides abundant reactive sites uniformly distributing the highly-ordered MOF-derived nanocubes. Benefitting from the unique porous structure, the FeP/C nanocubes exhibit remarkable sodium storage performance in terms of high capacity (410 mA h g−1, 100 mA g−1), excellent rate capacity (up to 1 A g−1) and long cycle life (> 200 cycles). The electrochemical reaction mechanisms of the FeP/C composite upon sodiation/desodiation are investigated in detail via ex-situ XRD, SEM and TEM methods, which show that the sodium storage in FeP is based on both the intercalation/conversion reactions. In addition, FeP/C as HER electrodes maintain its reactivity for at least 40 h and exhibit an low onset overpotential of 80 mV and a low Tafel slope of 40 mV dec−1. These results reveal the sodium storage mechanism of FeP and suggest that the MOF-derived FeP/C composite is a promising candidate for high-performance SIBs and HER electrode material.